2011
DOI: 10.3390/molecules161210214
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Glycation and Anti-Inflammatory Activities of Phenolic Constituents from Cordia sinensis

Abstract: Nine compounds have been isolated from the ethyl acetate soluble fraction of C. sinensis, namely protocatechuic acid (1), trans-caffeic acid (2), methyl rosmarinate (3), rosmarinic acid (4), kaempferide-3-O-β-D-glucopyranoside (5), kaempferol-3-O-β-D-glucopyranoside (6), quercetin-3-O-β-D-glucopyranoside (7), kaempferide-3-O-α-L-rhamnopyranosyl (1→6)-β-D-glucopyranoside (8) and kaempferol-3-O-α-L-rhamno-pyranosyl (1→6)-β-D-glucopyranoside (9), all reported for the first time from this species. The structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 30 publications
(34 reference statements)
3
52
0
4
Order By: Relevance
“…C. macleodii and C. nodosa have a wide distribution in tropical America (Izzo and PetInI-BenellI, 2011). C. sinensis, C. superba and C. thaisiana are found in the drier areas of India, Africa and Saudi Arabia (Al-Musayeib et al, 2011;Araque et al, 2009). C. abyssinica, C. africana, C. alliodora are species that have wood utilized in production of high-quality furniture and other objects and domestic utensils.…”
Section: Occurrence and Distributionmentioning
confidence: 96%
See 2 more Smart Citations
“…C. macleodii and C. nodosa have a wide distribution in tropical America (Izzo and PetInI-BenellI, 2011). C. sinensis, C. superba and C. thaisiana are found in the drier areas of India, Africa and Saudi Arabia (Al-Musayeib et al, 2011;Araque et al, 2009). C. abyssinica, C. africana, C. alliodora are species that have wood utilized in production of high-quality furniture and other objects and domestic utensils.…”
Section: Occurrence and Distributionmentioning
confidence: 96%
“…C. rufescens is used in medicine popular as an abortifacient and antiinflammatory (Costa et al, 2008). The stem bark of C. sinensis is used in traditional medicine for the treatment of gastric and respiratory disturbances (Al-Musayeib et al, 2011). C. globosa is utilized in traditional medicine in Paraiba State, Brazil for digestive problems, rheumatism and menstrual colic.…”
Section: Traditional Application and Biological/pharmacological Activmentioning
confidence: 99%
See 1 more Smart Citation
“…All the parts of this plant used as popular medicine when the stem bark of Cordia is used in traditional medicine for the treatment of gastric and respiratory disturbances [5]. In the Alagoas State, the leaves and flowers are used as treatment of hemorrhaging, throat infections and cold [6], also the leaves and roots of Cordia are used in folk medicine for digestive disturbances, rheumatism and as a generaltonic [7], besides the treatment of symptoms of menstrual colic and dyspepsia [8]- [9]- [10], so the leaves and stem of Cordia are used for various superficial inflammatory processes in wound areas and general inflammations and also as an analgesic for menstrual colic [11]. The survey concluded that no anatomical studies were carried on this genus in Iraq or abroad.…”
Section: Introductionmentioning
confidence: 99%
“…4-hydroxy-transcinnamate ester 8,13 , β-sitosterol 4,14 , quercetin and quercitrin 11,15 ). Preliminary phytochemical analysis of C. dichotoma bark indicated the presence of allantoin, β-sitosterol and 3', 5-dihydroxy-4'-methoxy flavanone-7-O-alpha-L-rhamnopyranoside 4,16 .…”
Section: Botanical Descriptionmentioning
confidence: 99%